2021
DOI: 10.1002/uog.23703
|View full text |Cite
|
Sign up to set email alerts
|

Automated quantitative evaluation of fetal atrioventricular annular plane systolic excursion

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Using both anatomic and conventional M-mode, increase in fMAPSE throughout the course of gestation has previously been reported from researches conducted in other parts of the world, and our findings are in tandem with these reports [4,8,9,11,15,16] . This radiological feature of the foetal left ventricular function in normal pregnancy has not yet been extensively investigated, especially in Nigeria.…”
Section: Discussionsupporting
confidence: 91%
“…Using both anatomic and conventional M-mode, increase in fMAPSE throughout the course of gestation has previously been reported from researches conducted in other parts of the world, and our findings are in tandem with these reports [4,8,9,11,15,16] . This radiological feature of the foetal left ventricular function in normal pregnancy has not yet been extensively investigated, especially in Nigeria.…”
Section: Discussionsupporting
confidence: 91%
“…After considering the four aspects of the right heart function measurement comprehensively, i.e., repeatability, the size of the measurement error, the measurement stability, and the reliability of the right heart function evaluation, we finally chose two indicators, namely the TAPSE value and the Tei index. It is believed that the TAPSE value can be used as an important parameter to evaluate the fetal right heart contraction function, and it has good reproducibility and lower requirements for equipment ( Herling et al, 2021 ; Messing et al, 2013 ). In this study, the numerical measurement was observed to be more dependent on the angle of the sampling line and the flow direction.…”
Section: Discussionmentioning
confidence: 99%
“…19 Herling et al investigated 35 FGR cases and demonstrated that TAPSE and MAPSE were substantially lower than AGA fetuses. 20 Crispi et al suggested that parameters reflecting longitudinal function such as TAPSE are typically affected in the very early stages compared to radial functions such as ejection fraction. Therefore, TAPSE is a more sensitive parameter that has been proposed for earlier diagnosis and monitoring of fetal cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…They found that TAPSE was significantly lower in FGR cases than infant hypertension and arterial remodeling 19 . Herling et al investigated 35 FGR cases and demonstrated that TAPSE and MAPSE were substantially lower than AGA fetuses 20 . Crispi et al suggested that parameters reflecting longitudinal function such as TAPSE are typically affected in the very early stages compared to radial functions such as ejection fraction.…”
Section: Discussionmentioning
confidence: 99%